Association Between Hemagglutination Inhibition Antibody Titers and Protection Against Reverse-Transcription Polymerase Chain Reaction–Confirmed Influenza Illness in Children 6–35 Months of Age: Statistical Evaluation of a Correlate of Protection. (25th September 2021) - Danier, Jasur; Callegaro, Andrea; Soni, Jyoti; Carmona, Alfoso; Kosalaraska, Pope; Rivera, Luis; Friel, Damien; Pu, Wenji; Vantomme, Valerie; Dbaibo, Ghassan; Innis, Bruce L; Schuind, Anne; et al.
Abstract: Background: Data from a randomized controlled efficacy trial of an inactivated quadrivalent influenza vaccine in children 6–35 months of age were used to determine whether hemagglutination inhibition (HI) antibody titer against A/H1N1 and A/H3N2 is a statistical correlate of protection (CoP) for the risk of reverse-transcription polymerase chain reaction (RT-PCR)–confirmed influenza associated with the corresponding strain. Methods: The Prentice criteria were used to statistically validate strain-specific HI antibody titer as a CoP. The probability of protection was identified using the Dunning model corresponding to a prespecified probability of protection at an individual level. The group-level protective threshold was identified using the Siber approach, leading to unbiased predicted vaccine efficacy (VE). A case-cohort subsample was used for this exploratory analysis. Results: Prentice criteria confirmed that HI titer is a statistical CoP for RT-PCR–confirmed influenza. The Dunning model predicted a probability of protection of 49.7% against A/H1N1 influenza and 54.7% against A/H3N2 influenza at an HI antibody titer of 1:40 for the corresponding strain. Higher titers of 1:320 were associated with >80% probability of protection. The Siber method predicted VE of 61.0% at a threshold of 1:80 for A/H1N1 and 46.6% at 1:113 for A/H3N2. Conclusions: The study validated HI antibody titer as a statistical CoP, by demonstrating that HI titer is correlated with clinical protection against RT-PCR–confirmed influenza associated with the corresponding influenza strain and is predictive of VE in children 6–35 months of age. Clinical Trials Registration: NCT01439360. Abstract : Strain-specific hemagglutination inhibition antibody titer is a statistical correlate of protection against RT-PCR–confirmed influenza associated with the corresponding influenza strain in children 6–35 months of age. The Dunning model predicted probability of protection against illness of 43.2%–60.2% at a titer of 1:40.